New distribution records, habitat description and comments on the natural history of the poorly known frog Atelognathus solitarius (Anura, Batrachylidae) from northwestern Patagonia, Río Negro Province, Argentina - Barrasso, Diego Andrés (2020)
Atelognathus solitarius is probably the least-known species of its genus. The species was described in 1970 based on a single specimen from the Las Bayas Creek, Río Negro Province, Argentina; later publications that reported new specimens did not provide new localities. Here, we present an update of its distribution, describe the habitats it occupies, detail features of its natural history, and discuss conservation aspects. For this purpose, all available records were compiled from herpetological collections, literature, and new data obtained during field trips to the type locality and surroundings. We confirmed the presence of the species near its type locality and extended the known distribution about 30 km WSW and 30 km NW. Furthermore, we discovered that in addition to using small streams, A. solitarius uses lagoons in volcanic tablelands. Future studies on the biological and ecological aspects of the species are essential to update the current conservation category of ‘Insufficiently Known’ for Argentinean categorization or ‘Data Deficient’ for IUCN.